Modeling roan and sable patterns of spatial distribution in the Mudumu National Park, Namibia - LineekelaOmwene T. Nauyoma; Christopher T. Rota; Frederico G. Lemos; Fernanda C. Azevedo; Fernando Sequeira; Ezequiel C. Fabiano (Wildlife Society Bulletin)
Abstract Large ungulates across the world are threatened with extinction due to habitat loss, land use change, and other anthropogenic pressures. While conservation measures are critical, for many populations the implementation of conservation measures is often not practical, either due to a lack of information on the species' biology or their conservation status. Here we consider 2 large ungulates, the roan (Hippotragus equinus) and sable (H. niger) antelopes, occurring in Mudumu National Park (MNP) Namibia, for which data on populations trends and habitat use are largely unknown. Here, we used camera trapping data collected in the dry and wet seasons between March and September 2021 in visit frequency models to understand the relationship between habitat variables and the distribution dynamics of roan and sable over time at MNP. Our results showed that roans in the wet season were detected more at sites with increased grass cover and detected less at sites near the Kwando River. In the dry season, roans were detected more at sites with increased grass cover and more termite mounds but detected less at sites near the Kwando River. In the wet season, sables were detected more at sites with fewer termite mounds. In the dry season, sables were detected more at sites with increased grass cover. We hypothesized that roan and sable use fewer areas near permanent water to avoid high predator densities and high grazing intensity by dense herds of short‐grass grazers. The study findings are useful knowledge on 2 threatened ungulates and will be used to inform and develop comprehensive conservation programs and strategies that aim to lower the risk of extinction for roan and sable at a Namibian protected area.